Strategic Nuclear Sharing - Schofield, J. author. aut Link
IX, 217 p.
Keywords: The sharing of nuclear weapons technology between states is unexpected, because nuclear weapons are such a powerful instrument in international politics, but sharing is not rare. This book proposes a theory to explain nuclear sharing and surveys its rich history from its beginnings in the Second World War.